(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2025)
What is our relationship with the material world around us? Do we passively consume it or do we engage with it and make something with it? This paper will examine the existential meaning of our relationship with the material world and how our relationship with it can have a dramatic effect on how we are, how we can be and how we can effect change in the world around us.